Global warming will happen faster than we think - Xu, Yangyang; Ramanathan, Veerabhadran; Victor, David G. (Nature (London), 2018)
Three trends will combine to hasten it, warn Yangyang Xu, Veerabhadran Ramanathan and David G. Victor. Global warming will happen faster than we think Three trends will combine to hasten it, warn Yangyang Xu, Veerabhadran Ramanathan and David G. Victor.